2014
DOI: 10.1590/0074-0276140019
|View full text |Cite
|
Sign up to set email alerts
|

The first report of the vanC1 gene in Enterococcus faecium isolated from a human clinical specimen

Abstract: The vanC1 gene, which is chromosomally located, confers resistance to vancomycin and serves as a species marker for Enterococcus gallinarum. Enterococcus faecium TJ4031 was isolated from a blood culture and harbours the vanC1 gene. Polymerase chain reaction (PCR) assays were performed to detect vanXYc and vanTc genes. Only the vanXYc gene was found in the E. faecium TJ4031 isolate. The minimum inhibitory concentrations of vancomycin and teicoplanin were 2 µg/mL and 1 µg/mL, respectively. Real-time reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…These include carbapenemase genes bla IMP-1 , bla IMP-2 , bla OXA-23 , aminoglycoside resistance gene aphA , and vancomycin resistance gene vanC . The vanC is a chromosomally located gene generally associated with the Gram-positive Enterococcus gallinarum and was recently detected in Enterococcus faecium (Sun et al, 2014). Since both E. faecium and Enterococcus faecalis were detected on Chromocult coliform agar, the presence of vanC in hospital wastewater is not unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…These include carbapenemase genes bla IMP-1 , bla IMP-2 , bla OXA-23 , aminoglycoside resistance gene aphA , and vancomycin resistance gene vanC . The vanC is a chromosomally located gene generally associated with the Gram-positive Enterococcus gallinarum and was recently detected in Enterococcus faecium (Sun et al, 2014). Since both E. faecium and Enterococcus faecalis were detected on Chromocult coliform agar, the presence of vanC in hospital wastewater is not unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…vanC is less virulent than vanA and vanB and intrinsically present in some enterococcal species. However, the vanC 1 gene cluster has been recently detected in E. faecalis and E. faecium clinical isolates providing moderate level resistance to vancomycin 55,56. Variable rates of vancomycin resistance were detected across the world, with lower rates detected in Europe and Canada (4%–6%) 54,57,58.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired resistance of enterococci to glycopeptides is induced by plasmid-mediated expression of Van operons. To date, nine different operons have been identified, of which VanA and VanB are the most frequently encountered operons in VRE [ 20 , 21 ]. These operons encode for enzymes that modify the peptidoglycan precursor d -Ala- d -Ala dipeptide and thereby substantially decrease the affinity of vancomycin to its target site (up to 1000-fold) [ 22 , 23 ].…”
Section: Chemistry and Mechanism Of Actionmentioning
confidence: 99%
“…However, recent studies identified the VanC gene in an E. faecium strain and therefore suggest that even VanC-type resistance can be transferred from one species to another. Activity of telavancin against VanC-type enterococci has not been investigated yet, but teicoplanin remains potent against them [ 21 23 , 25 30 ].…”
Section: Chemistry and Mechanism Of Actionmentioning
confidence: 99%